Dr Jacek Ladorucki — wspomnienie - Alina Brzuska-Kępa (Literatura i Kultura Popularna)
The article offers a reminescence about Jacek Ladorucki, Ph.D: an employee of the University of Łódź, a bibliologist, bibliophile, and researcher of books, literature and popular culture. Jacek Ladorucki died suddenly on June 28, 2023.